Productivity, Efficiency, and Convenience of Tourism Management Students in Online Education versus Traditional Education - Mark Gabriel Aguilar; Jayson Olayta; Victa Sari Dwi Kurniati (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2022)
The COVID-19 pandemic has caused changes in the global education system, requiring all educational institutions to adapt online instruction in response to government regulations such as lockdowns, travel restrictions, and the ban of public meetings, among others. As the country recovers from the effects of this pandemic, the Philippine government has chosen to return educational institutions' activities to face-to-face mode. During the pandemic, several academics sought to learn about the influence of online education on students' academic achievement, students' attitudes about online learning, the impact on students' mental health, and parents' perceptions and experiences. However, despite the abundance of published material, there is a lack of studies on students' preference between online education and traditional education, notably among tourism management students in the Philippines, as well as studies that have determined the differences on students' choice in terms of the type of institution they are enrolled at, motivating the researchers to conduct this study. Using a descriptive research design taking on quantitative research approach, the researchers aimed to determine the experience of tourism management students in selected colleges and universities in Region IV-A, Philippines towards online and traditional education in terms of productivity, efficiency, and convenience. Findings of this study serve as guide for government agencies concerned with education and educational institutions to understand their stakeholder, allowing them to come up with more preferable policy decisions in the future.